Linoleic Acids Overproducing Lactobacillus casei Limits Growth, Survival, and Virulence of Salmonella Typhimurium and Enterohaemorrhagic Escherichia coli - Peng, Mengfei; Tabashsum, Zajeba; Patel, Puja; Bernhardt, Cassandra; Biswas, Debabrata (Frontiers in Microbiology, 2018)
Probiotics, particularly lactic acid bacteria, are biologic agents which limit the growth, virulence, and survival/colonization of various enteric bacterial pathogens and serve as potential alternatives to antibiotics. Mechanisms that contribute to this antimicrobial effect include producing bioactive metabolites/acids, increasing nutrient and receptor-mediated competition, and modulating gut microbiome ecology. However, these functions of common probiotic strains are limited due to the finite quantity of metabolites they produce and their total number in the gut ecosystem. Conjugated linoleic acids (CLAs), critical metabolites of Lactobacillus, have multiple beneficial effects on human health including anti-carcinogenesis, anti-inflammation, anti-oxidation, and anti-pathogenicity. In this study, we aim to overexpress the myosin cross-reactive antigen gene (mcra) in Lactobacillus casei (LC) to enhance the production of CLA and investigate its effectiveness against enteric bacterial pathogens, specifically Salmonella enterica serovar Typhimurium (ST) and enterohaemorrhagic Escherichia coli (EHEC). By inserting mcra in L. casei, we generated LC-CLA and found the total linoleic acid production by an individual bacterial cell was raised by 21-fold. The adherence ability of LC-CLA on human intestinal cells increased significantly and LC-CLA competitively excluded both ST and EHEC in a mixed-culture condition. Furthermore, LC-CLA significantly altered the physicochemical properties, biofilm formation abilities, interactions with host cells of both ST and EHEC, and triggered anti-inflammatory activities of host cells. These findings offer insights on applying a genetically engineered probiotic to control gut intestinal infections caused by ST and EHEC and prevent foodborne enteric illness in human.